2013
DOI: 10.1111/exd.12223
|View full text |Cite
|
Sign up to set email alerts
|

E6 and E7 of human papillomavirus type 18 and UVB irradiation corporately regulate interleukin‐6 and interleukin‐8 expressions in basal cell carcinoma

Abstract: The lack of a human papillomavirus (HPV)-infected skin cancer cell line has hampered the investigation of the interaction of UV and HPV in skin carcinogenesis. We identified a human basal cell carcinoma (BCC-1/KMC) cell line integrated with E6 and E7 genes of high-risk HPV type 18 and demonstrated that repression of E6 and E7 results in proliferation inhibition. Sublethal ultraviolet-B (UVB) irradiation induced the expressions of interleukin-6 (IL-6) and interleukin-8 (IL-8), as well as viral E6 and E7 genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…UV-induced oxidative stress affects the generation/activation of both the signaling molecules associated with the kinase signaling cascade and the transcription factors such as Nrf2 that induce the biosynthesis of new proteins responsible for cell protection against DNA mutations, metabolic disorders, and apoptosis [3,10]. UV radiation also affects the cells' defense response via the modification of inflammatory protein mediators such as TNFa and interleukins [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…UV-induced oxidative stress affects the generation/activation of both the signaling molecules associated with the kinase signaling cascade and the transcription factors such as Nrf2 that induce the biosynthesis of new proteins responsible for cell protection against DNA mutations, metabolic disorders, and apoptosis [3,10]. UV radiation also affects the cells' defense response via the modification of inflammatory protein mediators such as TNFa and interleukins [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…An increase was observed in IL-6 secretion in studies conducted on cervical cells and other tissues infected with high-risk HPV subtypes. This increase in production and secretion, as in the case of IL-8, is made up of two direct and indirect routes, which were mediated by IL-17 (Hsiao et al, 2013;Ren et al, 2013). The serum or extracellular levels of IL-6 and IL-8 vary under various conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Cheng et al have observed an up-regulatory effect of HPV16 and HPV18 E6 and E7 to IL-6 expression in E6 and E7 transfected lung cancer cells (33). Also, the repression of HPV18 E6 and E7 in basal cell carcinoma cells reduced IL-6 expression levels (34). In addition, Dell'Oste et al reported an increase in IL-6 mRNA expression and protein secretion in primary keratinocytes immortalized with both E6E7 genes from HPV16 compared to control keratinocytes (20).…”
Section: Discussionmentioning
confidence: 99%